2018
DOI: 10.1002/mgg3.474
|View full text |Cite
|
Sign up to set email alerts
|

Clinical genetics and genomic medicine in Qatar

Abstract: Clinical genetics and genomic medicine in Qatar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…We also referred the father and sister to the adult rheumatology department for further evaluation, as the clinical phenotype could have been either subtle or overlooked. Coexisting genetic disorders have been reported in Arabic families [12,13], and WES has the advantage of detecting more than one disease, whether it has overlapping clinical features or independent clinical manifestations. WES has a high diagnostic yield in the setting of Mendelian disorders and is particularly helpful diagnostically in the highly consanguineous Middle Eastern population including the United Arab Emirates [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…We also referred the father and sister to the adult rheumatology department for further evaluation, as the clinical phenotype could have been either subtle or overlooked. Coexisting genetic disorders have been reported in Arabic families [12,13], and WES has the advantage of detecting more than one disease, whether it has overlapping clinical features or independent clinical manifestations. WES has a high diagnostic yield in the setting of Mendelian disorders and is particularly helpful diagnostically in the highly consanguineous Middle Eastern population including the United Arab Emirates [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…The QF is the main scientific body in Qatar that was founded in 1995 to serve the people of Qatar by supporting and operating programs in three core mission areas: education, science and research, and community development. QF Research, Development, and Innovation (QF RDI) is a division of QF that is responsible for supporting and funding different kinds of research activities through the following entities: Qatar Science and Technology Park, Qatar Biobank for Medical Research, Qatar Genome Programme, Qatar Biomedical Research Institute, Sidra Medicine, Doha International Family Institute, and World Innovation Summit for Health [12,13].…”
Section: Qatar Foundation (Qf)mentioning
confidence: 99%
“…It was founded in 1999 for the welfare of people with intellectual disabilities, mainly autism spectrum disorders. The center provides both clinical genetic and molecular diagnostic services in addition to conducting both independent and collaborative research projects [12,13].…”
Section: Shafallah Centre For Children With Special Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of the National Premarital Genetic Screening Program for a number of diseases, including CF, represents one notable milestone that started in 2009. Other diseases screened based on high carrier frequency include: thalassemia, sickle cell disease, classical homocystinuria and spinal muscular dystrophy [49]. Despite the importance of such screening programs, a recent study showed low knowledge and attitudes towards these programs in the Qatari population.…”
Section: Future Directions and Recommendationsmentioning
confidence: 99%